Corrosion evaluation and prediction in reinforced concrete specimens - Juan, Setiadi (2012)
Corrosion of steel reinforcements has always been one major problem for reinforced concrete structure and numerous efforts have been carried out to tackle the problem. This report aims to study the factors that may affect chloride induced corrosion rate of a reinforced concrete structure by analyzing the data from various past research data. Only corrosion rate research data which is measured by using Linear Polarization Resistance method from concrete specimens immersed into chloride solution is analyzed thoroughly in this report, data from other type of test conditions is not analyzed.